Improving partial wetting resolution on flexible substrates for application of polymer optical waveguides - Hoffmann, Gerd-Albert; Wolfer, Tim; Reitberger, Thomas; Franke, Jörg; Suttmann, Oliver; Overmeyer, Ludger (Optical Engineering, 2017)
Considering the increasing amount of data for communication and infotainment applications, fabrication of optical networks and bus systems is a challenging task for production engineering. A two-step manufacturing process for polymer optical waveguides is presented. By improving the highly efficient flexographic printing technology by laser functionalization of the printing tool in combination with a subsequent spray application, high-quality waveguides are accomplished. By adjusting the resulting surface energy of the foil substrate in the first fabrication process, the spray application achieved high-aspect ratio waveguides with a low attenuation of 0.2 dB/cm at 850 nm.
CRIS-Team Scopus Importer:2023-03-07
Keywords: flexographic printing; laser functionalizing; partial wetting; polymer optical waveguides